2021
DOI: 10.3390/app11072909
|View full text |Cite
|
Sign up to set email alerts
|

Research on a Piezoelectric Pump with Flexible Valves

Abstract: Imitating the structure of the venous valve and its characteristics of passive opening and closing with changes in heart pressure, a piezoelectric pump with flexible valves (PPFV) was designed. Firstly, the structure and the working principle of the PPFV were introduced. Then, the flexible valve, the main functional component of the pump, was analyzed theoretically. Finally, an experimental prototype was manufactured and its performance was tested. The research proves that the PPFV can achieve a smooth transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…7,8 The bionic type has an imitation fishtail type and built-in compliant structure. [9][10][11] Regardless of the structural form, the primary concern is how to maximize the positive and negative flow difference. In this article, through the simulation and comparison of the previous hemispherical and imitations of meniscus resistance fluids, it is found that the forward and backward flow resistance difference of the two fluids is small, and the output capacity of one-way flow is not enough.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The bionic type has an imitation fishtail type and built-in compliant structure. [9][10][11] Regardless of the structural form, the primary concern is how to maximize the positive and negative flow difference. In this article, through the simulation and comparison of the previous hemispherical and imitations of meniscus resistance fluids, it is found that the forward and backward flow resistance difference of the two fluids is small, and the output capacity of one-way flow is not enough.…”
Section: Introductionmentioning
confidence: 99%
“…However, the problems of high processing difficulty and the bulky shape of the two forms are obvious. Other forms, such as the flexible film valve [ 29 ], cymbal-shaped slotted valve [ 30 ], and venous imitation valve, have also been presented [ 31 , 32 ]. Moreover, the poor precision of the valve body and the insufficient cut-off are their common shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, valve piezoelectric pumps and valve-less piezoelectric pumps still have some limitations, which hinder their popularization and application. On the basis of the principle that the structure of cardiac valves prevents the blood from flowing back, a kind of piezoelectric pump with cardiac-valve-like structures (PPCVLS) was proposed in our previous study [ 29 , 30 ]. The working conditions of valve-based and valve-less pumps can be converted by only changing the driving voltage.…”
Section: Introductionmentioning
confidence: 99%